Implementasi Ketahanan Ekonomi Melalui Peningkatan Perdagangan Pemulihan Usaha Koperasi dan UMKM di Sekitar Kantor Walikota Medan - Alivia Azzahra; Andri Soemitra (Trending: Jurnal Manajemen dan Ekonomi, 2024)
Economic resilience is one of the important pillars in the development of a region. Medan City, as one of the economic centers in North Sumatra, has a strategic role in advancing the regional economy. Medan City, as one of the economic centers in North Sumatra, faces its own challenges in building local economic resilience, especially in the area around the Medan Mayor's Office, which is the center of government and economic activities. This article discusses the implementation of economic resilience through the enhancement of trade as well as the restoration of cooperatives and Micro, Small, and Medium Enterprises (MSMEs) businesses around the Medan Mayor's Office. The research aims to explore the various initiatives and strategies that have been implemented by the city government in supporting local economic development, particularly in the context of cooperatives and MSMEs. The results show the success of the program in supporting local economic growth, although there are challenges that still need to be addressed. Keywords: Economic Resilience, Trade, Cooperatives, MSME